Comprehensive evaluation of technical support capacity for occupational disease surveillance and assessment of CDCs in Sichuan Province, China - Yumin Li; Xia Li; Li Lin; Enfei Jiang (BMC Health Services Research)
Abstract Background When the health administration department re-assumed the responsibilities for occupational safety and health supervision and management in 2018, the Chinese government allocated special funds annually to the Centers for Disease Control and Prevention (CDCs) at all levels to enhance their capacity to monitor occupational diseases and hazardous factors. Thus, the CDCs’ technical support capacity for occupational disease surveillance and assessment (TSCODSA) has garnered increasing attention. Against this backdrop, we aimed to develop a comprehensive evaluation model to assess the CDCs’ TSCODSA, taking the municipal and county-level CDCs in Sichuan Province as an example. Methods In 2023, a survey was conducted on the municipal and county-level CDCs across 21 cities (including three autonomous prefectures) in Sichuan Province. Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) was used to evaluate the TSCODSA of these CDCs, combined with the Rank Sum Ratio (RSR) method for classification. The obstacle degree model was used to analyze the primary factors influencing their capacity. Results Among the 21 cities of Sichuan Province, only 4 cities (19.05%) had a “good” rating for the TSCODSA, while the remaining 17 cities (80.95%) were classified as either “medium” or “poor”. Cities with “good” ratings for the TSCODSA of CDCs were predominantly concentrated in the Chengdu Plain Economic Zone, while cities with “poor” ratings were mainly concentrated in the Northeast Sichuan Economic Zone. Obstacle degree analysis revealed that core capacity building and human resources constitute significant barriers impacting the capacity levels of CDCs across cities. Conclusion The overall TSCODSA level of CDCs in Sichuan Province is relatively low, with pronounced disparities in support capability across different economic zones, indicating imbalanced development. The evaluation system proposed in this study effectively reflects the level of TSCODSA of CDCs in various cities of Sichuan Province.